Cancer risk among farmers in the Nordic countries. (19th October 2011) - Kjærheim, Kristina; Martinsen, Jan Ivar; Lynge, Elsebeth; Gunnarsdottir, Holmfridur; Sparén, Pär; Tryggvadottir, Laufey; Weiderpass, Elisabete; Pukkala, Eero
Abstract : Objectives: Both the work and lifestyle of individuals engaged in agriculture may affect their cancer risk. The aim of this study was to describe cancer risk among male and female farmers in the Nordic countries. Methods: The study includes 622 000 men and 159 000 women aged 30–64 years registered as farmers in the 1960, 1970, 1980-1 and/or 1990 censuses in Denmark, Finland, Iceland, Norway and Sweden. During follow-up until 2003–5, 140 500 cancer cases were observed among men and 26 900 among women. The standardised incidence ratio (SIR) was computed as a ratio of observed and expected number of cases calculated from incidence rates for each country for the whole follow-up period and for the three periods 1961–75, 1976–90, and 1991–2005. Results: Overall cancer incidence among male (SIR=0.83, 95% CI 0.82 to 0.83) and female (0.84, 0.83 to 0.85) farmers was significantly lower than in the general population. Risk of multiple myeloma was slightly elevated in both genders (men: 1.07, 1.03 to 1.11, women: 1.14, 1.05 to 1.24), chronic lymphatic leukaemia in men only (1.09, 1.03 to 1.14). Risk of lip cancer was elevated among men in all countries (1.57, 1.51 to 1.62). For lung cancer (men: 0.56, 0.55 to 0.57, women: 0.46, 0.44 to 0.49) and upper aerodigestive tract cancers (men: 0.52, 0.51 to 0.35, women: 0.74, 0.69 to 0.79) risk was consistently low in both genders. Conclusions: While there are specific occupational risk factors in agricultural work, which deserve further attention, the general cancer pattern in this group points to work-related lifestyle factors which appear protective.